Guillain–Barré syndrome from an emergency department view: how to better predict the outcome?. (2nd November 2022) - Covino, Marcello; Romozzi, Marina; Simeoni, Benedetta; Di Paolantonio, Andrea; Sabatelli, Mario; Franceschi, Francesco; Luigetti, Marco
ABSTRACT: Objective: In Guillain–Barre syndrome (GBS), respiratory failure is the most serious manifestation and mechanical ventilation (MV) is required in approximately 20% of the patients. In this retrospective study, we aimed to evaluate clinical factors that can be evaluated in the Emergency Department which may influence the short-term prognosis of GBS patients. Methods: Data were acquired regarding age, sex, antecedent infections, neurological signs and symptoms, cerebrospinal fluid examination, nerve conduction studies, treatment of GBS, need for MV, length of stay in the hospital, and discharge destination (home or rehabilitation). Charlson Comorbidity Index and modified Erasmus GBS outcome score (mEGOS) were collected on admission. Results: Seventy-eight GBS patients were recruited with a mean age of 53.9 (range 19-81). Sixty-nine (88.46%) were diagnosed with GBS and nine (11.54%) had classic Miller-Fisher syndrome. Mean values for the Charlson Comorbidity index were 1.20 ± 1.81, and the values of mEGOS were 2.4 ± 1.6. The rate of home discharge and rehabilitation was similar between elderly and younger patients. Patients who required MV had higher mEGOS (p-value=0.061). Regarding the electrophysiological subtypes, we did not observe a significant difference between AIDP and AMAN/AMSAN concerning the need for MV, the type of discharge, values of mEGOS and Charlson Comorbidity Index. Discussion: A significant correlation was found between mEGOS and the need for MV. Age did not influence the short-term prognosis of GBS patients. mEGOS may be a useful tool for predicting outcomes in patients with GBS and higher mEGOS scores on admission significantly correlated with poor outcomes.